P-010 Optical Coherence Tomography (OCT) Before and After Flowdiverter Treatment in Basilar Dolichoectasia. (26th July 2014) - Brouwer, P; Ligthart, J; Regar, E
Abstract : Optical Coherence Tomography (OCT) is an endovascular imaging modality that utilises infrared light to create high-resolution images of the vascular system. The use of OCT in cardiology is widely accepted and considered safe for imaging of the coronary artery wall, plaques and assessment of stent deployment. In the literature to date, OCT has not been used in endovascular imaging of neurovascular pathology. In this report we describe the first case in which OCT was used to evaluate pathology and assess the quality of the flow diverter treatment both directly after the treatment and at five months follow. The use of OCT proved to be feasible in neurovascular pathology and rendered more information than was anticipated about both morphology, underlying pathology, and treatment result at the treatment date as well as five month follow up. Disclosures: P. Brouwer: 3; C; BALT extrusion, Paris. J. Ligthart: None. E. Regar: None.